Tracking human motion from monocular sequences - Snidaro, L.; Foresti, G. L.; Chittaro, L. (International Journal of Image and Graphics, 2008)
In recent years, analysis of human motion has become an increasingly relevant research topic with applications as diverse as animation, virtual reality, security, and advanced human-machine interfaces. In particular, motion capture Systems are well known nowa-days since they are used in the movie industry. These Systems require expensive multi-camera Setups or markers to be worn by the user. This paper describes an attempt to provide a markerless low cost and real-time solution for home users. We propose a novel approach for robust detection and tracking of the user's body joints that exploits different algorithms äs different sources of Information and fuses their estimates with particle filters. This System may be employed for real-time animation of VRML or X3D avatars using an off-the-shelf digital camera and a Standard PC.